EFFECTS OF IL-36Γ-MEDIATED P38 MAPK/ERK1/2 SIGNALING PATHWAY ON THE TISSUE REMODELING OF NASAL MUCOSA IN RATS WITH CHRONIC RHINOSINUSITIS - Jia Zeng; Xuejiao Li; Xiangsheng Li (Journal of Animal and Plant Sciences, 2026)
<p class="MsoNormal" style="text-align: justify; text-justify: inter-ideograph; line-height: normal; layout-grid-mode: char; mso-layout-grid-align: none; direction: ltr; unicode-bidi: embed; margin: 12.0pt 0in 0in 0in;">This study was aimed to investigate the effect of interleukin-36γ (IL-36γ) on nasal mucosal tissue remodeling in rats with chronic rhinosinusitis (CRS) through mediation of the p38 mitogen-activated protein kinase (p38 MAPK)/extracellular signal-regulated kinase 1/2 (ERK1/2) signaling pathway. Sixty healthy male rats were equally and randomly rolled into control group (sham operation + saline), CRS group (ovalbumin + lipopolysaccharide-induced CRS model), IL-36γ group (CRS model + intraperitoneal injection of IL-36γ inhibitor), MAPK group (CRS model + intraperitoneal injection of p38 MAPK inhibitor), IL-36γ negative control group (CRS model + inhibitor buffer), and p38 negative control group (CRS model + dimethyl sulfoxide buffer). Nasal symptoms and signs of the rats were regularly observed and recorded. The concentrations of IL-36γ, IL-1β, and TNF-α in serum were detected by enzyme-linked immunosorbent assay (ELISA). Nasal septum mucosal tissues were stained with hematoxylin and eosin (H&E) to observe histological structures, and eosinophils were manually counted using five randomly selected high-power fields per section. Alcian blue periodic acid schiff (AB-PAS) staining was performed to detect the number of goblet cells. Masson's trichrome staining determined the percentage area of collagen components. mRNA expression of three cytokines in rat nasal mucosa was detected by RT-qPCR. Western blotting detected expression changes of IL-36γ, key proteins of the MAPK pathway, and matrix metalloproteinase-9 (MMP-9) in nasal mucosa tissue. The nasal symptom scores were markedly increased in the CRS, IL-36γ, and MAPK groups versus controls (P<0.05). IL-36γ and MAPK groups exhibited a prominent reduction in nasal symptom scores, along with decreased eosinophil infiltration, goblet cell numbers, and collagen fiber deposition in nasal mucosa versus CRS group. IL-36γ, TNF-α, and IL-6 in both serum and nasal mucosa were reduced, and protein expression of IL-36γ, p-p38, p-ERK, and MMP-9 was substantially lower (P<0.05). The MAPK group demonstrated further reductions in serum and nasal mucosal levels of IL-1β, as well as in p-p38 and MMP-9 protein expression, versus the other treatment groups (P<0.05). Insignificant differences existed in all indicators among the IL-36γ negative control and the p38 negative control and the CRS groups (P>0.05). <p class="MsoNormal" style="text-align: justify; text-justify: inter-ideograph; line-height: normal; layout-grid-mode: char; mso-layout-grid-align: none; direction: ltr; unicode-bidi: embed; margin: 6.0pt 0in 0in 0in;">Conclusion: IL-36γ-mediated p38 MAPK/ERK1/2 signaling affects tissue remodeling of nasal mucosal in rats with CRS by regulating MMP-9 expression, showcasing a critical therapeutic target in CRS progression. Targeting this signal pathway may provide a new therapeutic strategy for improving nasal mucosa integrity and relieving inflammatory symptoms in CRS.<s> </s>
Keywords: chronic rhinosinusitis; nasal mucosa; tissue remodeling; IL-36γ; p38 MAPK/ERK1/2 pathway